The Effect of Social Media Promotion and Physical Evidence on Staying Decisions at Grage Hotel Bengkulu - Shintya Nurhofifah; Merri Anitasari; Yesi Indian Ariska (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
Along with the development of communication technology, almost all activities are carried out using technology ranging from communication, shopping transactions, promotions and others, so that it can facilitate the dissemination of information.. This study aims to find out the effect of promotion on social media and physical evidence on the decision to stay at the Grage Hotel Bengkulu. The method used in this study was a survey method with a quantitative approach. In this study the data analysis technique used was multiple linear regression. The population in this study were visitors to the Grage Hotel Bengkulu with a sample of 60 respondents. The results of this study are social media promotion factors that have a significant effect on the decision to stay at the Grage Hotel Bengkulu with a significance value of 0.009 <0.05. The physical evidence factor has a significant effect on the decision to stay at the Grage Hotel Bengkulu with a significance value of 0.000 <0.05. Social media promotion factors and physical evidence have a significant effect on the decision to stay at the Grage Hotel Bengkulu. This is evidenced by the statistical results of the F test of social media promotion factors and physical evidence obtained a significance value of 0.000 <0.05.